NILAI-NILAI ANTI KORUPSI DALAM CERITA RAKYAT ASAL USUL MALANG SEBAGAI GERAKAN LITERASI SEKOLAH - Mukhlishina, Innany; Murtyas Galuh Danawati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
The aim of this research is to describe anti-corruption values ​​in the folklore of the Origins of Malang as a school literacy movement. This research uses a qualitative approach with the type of discourse analysis research. The data collection technique used is the documentation study technique. The main instrument in this research is the human instrument. The research method was carried out using the content analysis method. The procedure is as follows: (1) read carefully the text of the Asal Usul Malang folklore repeatedly, (2) study key words related to anti-corruption values ​​in the Asal Usul Malang folklore, then (3) write down the values anti-corruption that appears in the folklore of the Origin of Malang. The anti-corruption values ​​that appear in the folklore of the Origin of Malang include honesty appearing four times, caring appearing once, independence appearing three times, discipline appearing four times, hard work appearing four times, and courage appearing six times. The anti-corruption values ​​that do not appear are responsibility, simplicity and fairness.